The culture of peace as a pillar of social sustainability - Ortega Jiménez, Mariola del Jesús (Emerging Trends in Education, 2026)
This is an interview with Dr. Ángel Alberto Valdés Cuervo, Senior Research Professor C at the Technological Institute of Sonora (ITSON), on the topic of “The culture of peace as a pillar of social sustainability.” In this conversation, the interviewee draws on his extensive experience to address the topic of the culture of peace in the Mexican context, particularly in higher education institutions (HEIs). In this conversation, the interviewee points out the coexistence of two types of peace in Mexico: positive and imperfect, noting that as a country, Mexico is in a transition to a culture of positive peace and is on the right track because actions and strategies aimed at this goal are being promoted. Similarly, he points out that the culture of peace is a fundamental pillar of social sustainability because without peaceful and just relationships there may be peace, but not social justice. In other words, in many places where there is marked repression, there are no demonstrations, but that is not fair; it is simply the imposition of an idea where power is being exercised...
Keywords: Culture of peace; Conflict